Biomass-to-bio-products application of feruloyl esterase from Aspergillus clavatus - Damásio, André R. L.; Braga, Cleiton Márcio Pinto; Brenelli, Lívia B.; Citadini, Ana Paula; Mandelli, Fernanda; Cota, Junio; De Almeida, Rodrigo Ferreira; Salvador, Victor Hugo; Paixao, Douglas Antonio Alvaredo; Segato, Fernando; Mercadante, Adriana Zerlotti; De Oliveira Neto, Mario [UNESP]; et al. (Springer Nature, 2013)
The structural polysaccharides contained in plant cell walls have been pointed to as a promising renewable alternative to petroleum and natural gas. Ferulic acid is a ubiquitous component of plant polysaccharides, which is found in either monomeric or dimeric forms and is covalently linked to arabinosyl residues. Ferulic acid has several commercial applications in food and pharmaceutical industries. The study herein introduces a novel feruloyl esterase from Aspergillus clavatus (AcFAE). Along with a comprehensive functional and biophysical characterization, the low-resolution structure of this enzyme was also determined by small-angle X-ray scattering. In addition, we described the production of phenolic compounds with antioxidant capacity from wheat arabinoxylan and sugarcane bagasse using AcFAE. The ability to specifically cleave ester linkages in hemicellulose is useful in several biotechnological applications, including improved accessibility to lignocellulosic enzymes for biofuel production. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Antioxidant capacity; Aspergillus clavatus; Feruloyl esterase; Phenolic compounds; Sugarcane bagasse; Wheat arabinoxylan; Sugar-cane bagasse; Bagasse; Esters; Polysaccharides; Enzymes; antioxidant; arabinoxylan; bagasse; esterase; ferulic acid; feruloyl esterase; hemicellulose; phenol derivative; unclassified drug; biomass; cell organelle; cellulose; enzyme activity; fungus; lignin; polysaccharide; resolution; sugar cane; X-ray; bacterial strain; biofuel production; circular dichroism; enzyme structure; Escherichia coli; nonhuman; nucleotide sequence; protein expression; protein purification; sugarcane; wheat; X ray crystallography; Triticum aestivum